2019
DOI: 10.15171/npj.2019.18
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant therapy to improve or resolve atherosclerosis; new hopes and current trends

Abstract: An introduction to atherosclerosis Coronary artery disease (CAD) is known major leading causes of death in developed countries over recent decades. It has been estimated that 15.5 million adults (6.2% of the adult population) are involved in CAD in the United States (1). Atherosclerosis is a chronic inflammatory vascular disease in arterial intima and established the major leading causes of death in the United States and Europe (2). The incidence of atherosclerosis is correlated with disorder of several biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…This condition comes with great costs for both the individual and society. Therefore, therapeutic strategies, including a range of dietary, supplements have been developed to improve the glycaemic control (3,42,43) . Among dietary supplements, Mg has aroused curiosity among the scientific community.…”
Section: Discussionmentioning
confidence: 99%
“…This condition comes with great costs for both the individual and society. Therefore, therapeutic strategies, including a range of dietary, supplements have been developed to improve the glycaemic control (3,42,43) . Among dietary supplements, Mg has aroused curiosity among the scientific community.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its rich antioxidant and anti-inflammatory content, it has been hypothesized that coffee consumption might be of benefit to cardiovascular health since oxidation and inflammation represent the important mechanisms in coronary artery disease (Rafieian-Kopaei, 2014). The anti-atherosclerotic property of antioxidants in prevention and improvement atherosclerosis had been reviewed by Yalameha (2019).…”
Section: Discussionmentioning
confidence: 99%
“…50,51 Recently, different evidence has strongly supported the positive relationship between the consumption of antioxidant-rich diets and cardiovascular health. [52][53][54] It has been observed that certain foods containing bioactive compounds, such as carotenoids and polyphenols, possess ameliorative and/or therapeutic effects against atherosclerotic lesions, ventricular remodelling, myocardial infarction, HF and MIRI. 36 In addition, antioxidant-rich natural products such as fruits, vegetables, cereals and nuts could upgrade cardiovascular health and decrease the risk of CVDs via regulating serum lipids, blood pressure, blood glucose and body weight as well as mitigating inflammation and OS.…”
Section: The Role Of Dietary-derived Antioxidants In Cvdsmentioning
confidence: 99%